Waspada Gangguan Pernapasan: Peran Skrining Spirometri dalam Pencegahan Penyakit Paru di Kelurahan Grogol - Kosasih, Robert; Santoso, Alexander Halim; Gunaidi, Farell Christian; Alvianto, Fidelia; Pratama, Aditya (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2025)
Lung health plays a vital role in maintaining individual productivity and metabolic functions, especially in adults. Early detection of pulmonary function decline is essential, as respiratory disorders such as chronic obstructive pulmonary disease (COPD) and asthma often develop insidiously. This community service program aimed to conduct early screening of lung function using spirometry in Grogol Subdistrict, West Jakarta, targeting the productive-age population. The activity followed a Plan-Do-Check-Act (PDCA) cycle, beginning with public education and proceeding to spirometry tests, result evaluations, and follow-up medical advice. A total of 71 participants were involved, with a mean age of 43.6 years. The average spirometric values were: Vital Capacity (VC) 2.32 L, Forced Vital Capacity (FVC) 2.09 L, Forced Expiratory Volume in 1 second (FEV1) 1.95 L, and FEV1/FVC ratio of 92.14%. Most participants (98.6%) were categorized as "normal/at risk", with only 1.4% suspected of having a pulmonary disorder. These findings underscore the importance of routine lung health monitoring in asymptomatic individuals. Through early screening and health education, this program contributes to increasing public awareness of respiratory health, promoting preventive strategies, and potentially reducing the burden of chronic lung diseases in the long term. Keywords: Lung Function, Spirometry, Early Detection, Chronic Obstructive Pulmonary Disease (COPD), Health Screening